ANALISIS KANDUNGAN LOGAM BERAT TIMBAL (Pb) DAN TEMBAGA (Cu) DI ALIRAN AIR SUNGAI BELUMAI, KECAMATAN TANJUNG MORAWA (Analysis Of The Content Of Heavy Metals Lead (Pb) And Copper (Cu) In River Water Flow Belumai, District of Tanjung Morawa) - Tagianto Ginting; Irwanmay Irwanmay; Eka Budiyulianto (AQUACOASTMARINE, 2014)
This research aims to analyze the content of Pb and Cu in the Belumai River basin as well as determine the quality of the river water raw water quality based on Belumai. This research was carried out in February-March, 2014 in the flow of the river Belumai, District of Tanjung Morawa. The number of the observed station point of 3 stations, with repetition as much as 3 times every 10 days. The observed parameters of physical-chemical parameters are waters, heavy metal content is analyzed using Atomic Abrsorption Spectrophotometry (AAS). The content of heavy metals lead (Pb) in may on the water between 0,074-0,176 mg/L and heavy metals of copper (Cu) on the water between 0,186-0,423 mg/l. This results indicate that the heavy metal content of Pb and Cu in Belumai River flow has exceeded the quality standard by Government Regulation no. 82 of 2001.Keywords : Heavy metals Pb, Heavy metals Cu, Water, Sediment, Belumai River